Entrepreneurs’ Characteristics from the Islamic Perspective: A Study of Muslimpreneurs’ Performance - Ismail, Anita; Laili Muda @ Ismail , Farah; Ab Wahab, Norailis; Abdul Latiff, Latifah; Muhammad Taky Eldin Kandil, Hisham (International Journal of Psychosocial Rehabilitation, 2020)
This research aims at identifying the Islamic characteristic factors of Muslim entrepreneurs in the business environment. The main sources of this study involve the adaptation characertistics of Muslim scholars in a business environment, including Quran, Hadith, narrations, academic study as well as other reliable sources. As such, this research is an attempt to explore the factors of Islamic characteristic elements of Muslimpreneurs, such as taqwa and planning, and it is hoped to contribute to the further development and understanding of this area in the humanities and social science fields. Moreover, the study will look at the objectives of Muslim entrepreneurs in Islam as part of fulfilling the duty of a vicegerent on earth, strengthening one’s relationship with Allah, finding truth, and serving the society. The findings revealed that significant relationships exist between the state of taqwa and planning among Muslimpreneurs in relation to business performance. These findings provide a distinctive perspective on the concept of taqwa and proper planning and its necessity in the Islamic system for the contemporary modern era. In addition, it recommends investigating the trend and profile of successful Muslimpreneurs and eventually developing global Muslimpreneurs. The outcomes and results of this study are then hoped to stimulate further improvements, advancements, and research on the subject matter.